Frequency of Post-Surgery Hypocalcaemia in Patients Undergoing Total Thyroidectomy - Muhammad Farooq, Muhammad Afzal, Muhammad Wahid Saleem, Sharbaz Hussain Khosa, Muhammad Omer Khan Balouch, Muhammad Shahzad Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out frequency of post-thyroidectomy hypocalcaemia among patients undergoing total thyroidectomy. Study Design: A prospective cohort study. Place and Duration: The Department of ENT, Shahida Islam Teaching Hosptial, Lodhran from January 2021 to December 2021. Methodology: A total of 181 patients of both genders aged 12-65 years with multinodular goiter, carcinoma thyroid or recurrent goiter and who were indicated total thyroidectomy were included. At the time of enrollment, demographic characteristics like gender, age and residential status were noted. Pre-surgery thyroid profile and serum calcium were measure from institutional laboratory. Standard procedure protocols were followed for total thyroidectomy. Post-surgery, measurement of serum calcium level was done after 24-hours and serum calcium level<8.0 mg/dL was labeled as hypocalcaemia. Results: In a total of 181 patients as per inclusion/exclusion criteria who underwent total thyroidectomy, 137 (75.7%) were female. Mean age was 43.6+8.2 years while 113 (62.4%) patients were aged between 40-60 years. Residential status of 98 (54.1%) patients was rural. Pre-surgery diagnosis was malignant in 41 (22.7%) patients while it was benign in 140 (77.3%) patients. Post-thyroidectomy hypocalcaemia was noted in 59 (32.6%) patients. Female gender (p=0.0251) and baseline hypertension (p=0.0287) were found to have significant association with post-thyroidectomy hypocalcaemia. Clinical Implications: Following patients of hypocalcaemia would certainly give us information about the proportion of transient hypocalcaemia and permanent hypocalcaemia. Conclusion: Frequency of post-thyroidectomy hypocalcaemia was found to be high (32.6%). Female gender and baseline hypertension were found to have significant association with post-thyroidectomy hypocalcaemia. Keywords: Calcium, carcinoma thyroid, hypertension, hypocalcaemia, multinodular goiter, thyroidectomy.